In vitro assessment of the influence of different protection plugs over obturation remnant space, after post preparation, on the retention of cast metal posts - Bueno, Carlos Roberto Emerenciano [UNESP]; Valentim, Diego [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP] (Dental Press International, 2020)
Objective: To evaluate the influence of different protection plugs over the remaining obturation after post space preparation, on cast metal post retention. Methodology: Fifty bovine teeth were decoronated and root canals were manually instrumented up to a Kerr 80 file and then obturated. A Largo drill was used to partially clear the canal at a 10mm depth. Groups were divided, according to different plug materials (n=10): Group I (control, with no plug), Group II (Coltosol® plug), Group III (Sealapex® + zinc oxide in putty-like consistence plug), Group IV (ethyl-cyanocrylate plug) and Group V (zinc phosphate plug). A layer with 1mm of thickness of different plug materials (Groups II, III, IV and V) was adapted over the remaining obturation and specimens were sealed and then stored in 100% humidity for 7 days. After the root canal was molded, cast metal posts were manufactured and cemented with zinc phosphate. The specimens remained in a humid chamber for 45 days before traction test was performed using a universal testing machine. The values were shown in Megapascal (MPa) and submitted to the ANOVA test and Tukey’s T est (P<.05). Results: Ethylcyanoacrylate reduced cast metal post retention (P<.01), without differences from the other groups (P>.05), similar to control. Conclusion: The obturation protection with plugs made of ethyl-cyanoacrylate hindered retention when cast metal posts are cemented with zinc phosphate, whereas Sealapex® with added zinc oxide, hardened zinc phosphate cement or Coltosol® do not interfere in the adhesiveness factor.
Keywords: Cementation; Dental Prosthesis Retention; Dental Pulp Cavity; Endodontics